Factors influencing successful establishment of exotic Pinus radiata seedlings with co-introduced Lactarius deliciosus or local ectomycorrhizal fungal communities - Wang, Ran; Wang, Yanliang; Guerin-Laguette, Alexis; Zhang, Peng; Colinas, Carlos; Yu, Fuqiang (Frontiers in Microbiology, 2022)
An introduction of exotic or non-native trees may fail due to lack of suitable fungal partners. We planted exotic Pinus radiata in a new habitat in Xifeng, Guizhou Southwest China. Strategies to introduce P. radiata seedlings either colonized with an ectomycorrhizal fungus (EcMF), Lactarius deliciosus, or expect them to form familiar/new associations with local EcMF in a new habitat were studied to know how P. radiata could be successfully established over a period of 2.5 years. Plant height and needle nutrient acquisition, persistence of co-introduced L. deliciosus and fungal community composition in rhizosphere soil and root tips were analyzed. In addition, a greenhouse bioassay experiment of local soil to assess the differences in the EcMF community between exotic and native pine seedlings was also conducted. The current results demonstrated that either co-introduced L. deliciosus or associations with local EcMF could both help P. radiata establish in Xifeng. The co-introduced L. deliciosus might be naturalized with P. radiata in the new area. Host identity had no effect on fungal composition since exotic P. radiata and native P. massoniana recruited similar local fungal communities, but L. deliciosus pre-colonization significantly altered the mycorrhizosphere fungal composition. The cosmopolitan species Suillus placidus, with high relative abundance, was found in the rhizosphere soil and root tips in the plantation. In addition, the greenhouse bioassay experiment further proved that a local EcMF, Suillus sp., contributed relatively higher extracellular enzymes by forming ectomycorrhizas with P. radiata, and there was no alteration of the fungal community caused by P. radiata during early establishment. Our study showed that exotic P. radiata could be a suitable tree capable to get established successfully in Xifeng either by interaction with co-introduced L. deliciosus or with local EcMF, while more attention should be paid to local EcMF community changes induced by the introduced L. deliciosus.